1999
DOI: 10.1074/jbc.274.18.12748
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Assembly of Rad51 and Rad52 Recombination Complex Requires ATM and c-Abl

Abstract: Cells from individuals with the recessive cancerprone disorder ataxia telangiectasia (A-T) are hypersensitive to ionizing radiation (I-R). ATM (mutated in A-T)is a protein kinase whose activity is stimulated by I-R. c-Abl, a nonreceptor tyrosine kinase, interacts with ATM and is activated by ATM following I-R. Rad51 is a homologue of bacterial RecA protein required for DNA recombination and repair. Here we demonstrate that there is an I-R-induced Rad51 tyrosine phosphorylation, and this induction is dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(154 citation statements)
references
References 37 publications
5
148
1
Order By: Relevance
“…However, whether the repair defects observed in c-AblÀ/À MEFs were mediated by the compromised activation of Atm/Atr needed further investigation. 14,34 Based on these findings, we propose the following model to explain a possible role for c-Abl in cell response to DSBs. Once DSBs occur, Atm is localized onto DSBs and is activated in a MRN complex-dependent but c-Abl independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the repair defects observed in c-AblÀ/À MEFs were mediated by the compromised activation of Atm/Atr needed further investigation. 14,34 Based on these findings, we propose the following model to explain a possible role for c-Abl in cell response to DSBs. Once DSBs occur, Atm is localized onto DSBs and is activated in a MRN complex-dependent but c-Abl independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, at concentrations resulting in a significant inhibition of DNA-PK-dependent NHEJ, wortmannin also inhibits ATM (Sarkaria et al, 1998). It has been shown that ATM regulates other proteins known to play a role in DNA-repair, cell-cycle regulation and radiation sensitivity, including p53, CHK2, BRCA1 and NBS1 (Canman et al, 1998;Cortez et al, 1999), and is required for the assembly of Rad51 foci (Chen et al, 1999;Yuan et al, 2003). Therefore, wortmannin should not only affect NHEJ through inhibition of DNA-PK activity in NSCLC cell lines , but also HR via inhibition of ATM-dependent formation of Rad51 foci.…”
Section: -Test)mentioning
confidence: 99%
“…44 It has been suggested that the IR signaling pathway that includes Atm and c-Abl, is required for modifying Rad51 to be assembled in a repair protein complex. 45 Also, direct interaction was demonstrated between c-Abl and DNA-PK. 31 The latter plays an essential role in DNA recombination.…”
Section: C-abl: Dna-binding and Transcriptionmentioning
confidence: 99%